Ohluchlí lidé mimo okruh zájmu sociálního začleňování - Liberdová, Eva (Univerzita Pardubice, 2011)
The text is about implications of deafness. Deafness create myth and prejudices, because public doesn't know communication needs adults, who turned deaf.
Keywords: integration; deafness; communication needs; non-delayed transcription; integrative egality; myth; labelling